STRATEGI PEMBELAJARAN NILAI-NILAI AGAMA DAN MORAL UNTUK MEMBENTUK KARAKTER RELIGIUS DAN MANDIRI DI RA TERPADU AL-MADINAH KECAMATAN BALONG KABUPATEN PONOROGO - Sularmi Sularmi; Bambang Harmanto; Anip Dwi Saputro (Universitas Muhammadiyah Ponorogo, 2020)
The purpose of this study is 1.) To identify the planning of learning religious and moral values to form religious and independent characters in RA Integrated Al-Madinah Kec. Balong Kab. Ponorogo, 2.) To identify learning strategies of religious and moral values to form religious and independent characters in RA Integrated Al-Madinah Kec. Balong Kab. Ponorogo, 3.) To identify the evaluation of learning strategies of religious and moral values to form religious and independent characters in RA Integrated Al-Madinah Kec. Balong Kab. Ponorogo. The research method used by the type of field research with the data source is the speakers, seeing the events at the location, and doing documentation, data collection techniques with participant observation, interviews, and documentation. The results in this study are 1.) The teachers make learning plans in the form of semester programs, weekly programs and daily programs. 2.) Learning strategy for the head of RA to make policy by opening role classes and practical life, making report cards and giving examples to students. For teachers in making religious and independent character formation through habituation in learning. For parents to provide assistance to their children. 3.) Evaluation is carried out, namely conducting daily assessments, and making assessment reports and follow-up. One of the findings from the study shows that the involvement or participation of students in learning activities is influenced by the fforts of the teacher, the environment and habituation